2021
DOI: 10.15218/ejnm.2021.01
|View full text |Cite
|
Sign up to set email alerts
|

Dialysis-Related Factors Affecting Activities of Daily Living among Hemo-dialysis Patients in Erbil City

Abstract: Background and objectives: Hemodialysis procedure is one of the important replacement therapies for patients with renal failure. Maintenance hemodialysis is associated with many complications that play a significant role in the activities of daily living. The present study aimed to find out the factors affecting activities of daily living among patients with maintenance hemodialysis in Erbil City in the Kurdistan Region of Iraq. Methods: The cross-sectional study was conducted on 268 patients undergoing mainte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…15 Studies have demonstrated that the risk of chronic renal failure development rises with age, a study done in Erbil shows that the age of most hemodialysis patients was 51 and above (68.3%). 16 This finding is close to our results which revealed that the highest rate of hemodialysis patients was 51-70 (55.7%) years old.…”
Section: Subjects Of the Studysupporting
confidence: 92%
See 2 more Smart Citations
“…15 Studies have demonstrated that the risk of chronic renal failure development rises with age, a study done in Erbil shows that the age of most hemodialysis patients was 51 and above (68.3%). 16 This finding is close to our results which revealed that the highest rate of hemodialysis patients was 51-70 (55.7%) years old.…”
Section: Subjects Of the Studysupporting
confidence: 92%
“…A study conducted by Ali et al 16 shows that most of the HD patients were males (51.5%) and live in urban areas (89.2%). This finding agrees with our results in that most of the HD patients were male (52.9%) and live in urban areas (58.6%).…”
Section: Table 4 Median (Interquartile Range) or Mean±standard Error ...mentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid complications from HD and to live a healthy and happy life, patients should increase their daily exercise and self-care. (Ali et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They are completely reliant on the availability of vascular access works (VA) and the establishment and successful use of access to the blood vessels, arteries, and veins necessitates a multidisciplinary team of learners to ensure a coordinated vasculature. 2 Majors in health behavior science study and analyze how human activities, cognitions, communications, and the environment affect health, relationships, chronic disease, and quality of life through time. They work to promote healthy lifestyles through education, policy change, needs assessment, program development, and implementation, individual counseling and coaching, media and materials creation, and evaluation of the impact and outcome of their efforts.…”
Section: Introductionmentioning
confidence: 99%